Doctors’ Self-Presentation Strategies and the Effects on Patient Selection in Psychiatric Department from an Online Medical Platform: A Combined Perspective of Impression Management and Information Integration - Xuan Liu; Xiaotong Chi; Jia Li; Shuqing Zhou; Yan Cheng (Journal of Theoretical and Applied Electronic Commerce Research)
Online medical consultation has become a crucial channel for patients seeking health support. Based on data from a psychiatric department in a leading online medical consultation platform in China, this study examines two possible types of online self-presentation strategies (positive impression management strategy and blending-in impression management strategy) employed by doctors in three dimensions: informational management, affective management, and image management, and explores their impact on patient selection. Meanwhile, an information integration perspective was incorporated and the interaction effects between impression management strategies taken by doctors and patient reviews expressed by online patients are also explored. Results indicate that the information quantity (representing the informational management dimension) in doctors’ profiles has a negative impact on patient selection (β = −0.142, p < 0.01), while the positive emotion expression (representing affective management) (β = 0.423, p < 0.01) and profile photo (representing image management) (β = 1.098, p < 0.01) positively influence patient selection. Patient reviews related to expertise positively moderate the effect of information quantity in doctors’ introduction on patient selection (β = −0.632, p < 0.05). In contrast, patient reviews concerning attitude (β = −0.882, p < 0.01) and credibility (β = −0.488, p < 0.01) negatively moderate the effect of emotion expression and profile photos on patient selection, respectively. The findings extend the applicability of impression management theory, providing a novel perspective for comprehending the impact of doctors’ self-presentation on patient selection and its interaction effect with patient impressions.